2005
DOI: 10.1142/s0217732305019055
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical Expansions, the Strong Quantum Limit, and Duality

Abstract: We show how to complement Feynman's exponential of the action so that it exhibits a Z2 duality symmetry. The latter illustrates a relativity principle for the notion of quantum versus classical.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…On the other hand, we have in ref. [6] shown that the existence of a minimal length scale L P is equivalent to the exchange…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we have in ref. [6] shown that the existence of a minimal length scale L P is equivalent to the exchange…”
Section: Introductionmentioning
confidence: 99%
“…In this letter we have established the equivalence between the duality (2) and that proposed in ref. [5], which can be summarised in eqn. (4).…”
Section: Discussionmentioning
confidence: 99%
“…As stressed in ref. [5], the auxiliary particle of mass m is not to be confused with the physical degrees of freedom of the action S under consideration in eqn. (3).…”
Section: Equivalence Of Dualitiesmentioning
confidence: 99%
“…[5] is equivalent to a Heisenberg-algebra noncommutativity [6] for the space coordinates. The connection on the gerbe is interpreted physically as a Neveu-Schwarz field B µν or, equivalently, as the magnetic background [7] that causes space coordinates to stop being commutative and close a Heisenberg algebra instead.…”
Section: Introductionmentioning
confidence: 99%
“…is closely related to the trivialisation of a gerbe on F. This fact can be used in order to prove that the semiclassical vs. strong-quantum duality S/ ↔ /S of ref. [5] is equivalent to a Heisenberg-algebra noncommutativity [6] for the space coordinates.…”
Section: Introductionmentioning
confidence: 99%